Well-being and participation of young leaders in rural areas of South-Western Europe. The project YouLeaders - De Angelis, Maria Chiara; Volpi, Valentina (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The current global scenario characterised by increasing complexity and the difficulty of imagining a present and a future for the generations to come is increasingly directing European policies towards researching and experimenting with intervention models that contribute to the promotion of the social, economic and environmental sustainability of territories and communities. The need for a systemic approach to change and innovation is all the stronger in rural areas, which are local administrative communities outside urban clusters, mostly characterised by a low population density on the territory, and by a specific socio-geographical, economic and cultural configuration, which calls for the constant development of specific services for young and old resident in the territory (CoE, 2022).